Breaking the missional code : your church can become a missionary in your community - Stetzer, Ed.; Putman, David (Nashville, Tenn. : Broadman & Holman, 2006)
"Across North America, many pastors are excited to see churches growing as they achieve their mission to connect the message of the gospel with the community at large. Still others are equally frustrated, following the exact same model for outreach but with lesser results. Indeed, just because a 'missional breakthrough' occurs in one place doesn't mean it will happen the same way elsewhere. One size does not fit all, but there are cultural codes that must be broken for all churches to grow and remain effective in their specific mission context. Breaking the Missional Code provides expert insight on church culture and church vision casting, plus case studies of successful missional churches impacting their communities. 'We have to recognize there are cultural barriers (in addition to spiritual ones) that blind people from understanding the gospel, ' the authors write. 'Our task is to find the right way to break through those cultural barriers without removing the spiritual and theological ones.'"--Jacket.
The emerging glocal context -- Breaking the missional code -- Responding to the commissions of Jesus -- The missional church shift -- Transitions to missional ministry -- Values of leaders and churches that break the code -- Contextualization : making the code part of your strategy -- Emerging strategies -- Spiritual formation and churches that break the code -- Revitalization to missional ministry -- Planting missional ministries -- Emerging networks : new paradigms of partnership -- Breaking the code without compromising the faith -- Best practices of leaders and churches that break the code -- The process of breaking the code -- Breaking the unbroken code.
Includes bibliographical references (pages 241-244).
Keywords: Evangelistic work; Pastoral theology